2018
DOI: 10.1016/j.dib.2018.05.100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of head and neck squamous cell carcinoma using iTRAQ based quantitative proteomic approach

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers in India. Despite improvements in treatment strategy, the survival rates of HNSCC patients remain poor. Thus, it is necessary to identify biomarkers that can be used for early detection of disease. In this study, we employed iTRAQ-based quantitative mass spectrometry analysis to identify dysregulated proteins from a panel of head and neck squamous cell carcinoma (HNSCC) cell lines. We identified 2468 proteins, of which 496 proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…HSPH1 has been reported as one of the many heat shock proteins detected to be abundant in the conditioned media of colon cancer cell lines [52]. A recent study carried out by our own group has reported the overexpression of HSPH1 in HNSCC cell lines CAL 27, FaDu and JHU-O28 in comparison with OKF6/TERT1 [53]. Furthermore, among the differentially secreted proteins we observed lower abundance of MMP9 in OKF6/TERT1-Shisha secretome compared to parental secretome.…”
Section: Discussionsupporting
confidence: 45%
“…HSPH1 has been reported as one of the many heat shock proteins detected to be abundant in the conditioned media of colon cancer cell lines [52]. A recent study carried out by our own group has reported the overexpression of HSPH1 in HNSCC cell lines CAL 27, FaDu and JHU-O28 in comparison with OKF6/TERT1 [53]. Furthermore, among the differentially secreted proteins we observed lower abundance of MMP9 in OKF6/TERT1-Shisha secretome compared to parental secretome.…”
Section: Discussionsupporting
confidence: 45%
“…Furthermore, we screened 20 genes as prognostic markers following DEFAMGs analysis. HPSH1 has been reported to be an early detected gene that can be used as a biomarker for HNSCC identification 27 . Similarly, the mRNA expression levels of LDHA isozymes were significantly greater in HNSCC compared to the controls 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the traditional experimental approaches, advances in high-throughput proteomics analysis can enable researchers to identify the total DEP profiles and abnormal pathological process of SBI after ICH to explore the potentially molecular and pathogenic mechanisms on the macro level. Particularly, further according experiments can be performed to verify the targeted data-derived research hypothesis [ 21 24 ]. However, no ICH proteomics studies have been published so far.…”
Section: Discussionmentioning
confidence: 99%